Transcranial Direct Current Stimulation Over Prefrontal Areas Improves Psychomotor Inhibition State in Patients With Traumatic Brain Injury: A Pilot Study - Zhang, Xu; Liu, Baohu; Li, Nan; Li, Yuanyuan; Hou, Jun; Duan, Guoping; Wu, Dongyu (Frontiers in Neuroscience, 2020)
Objectives: Many post-traumatic patients with minimally conscious state are complicated by psychomotor inhibition state (PIS), which impedes further rehabilitation. The treatment of PIS is not satisfactory. This study aimed to investigate effects of anodal transcranial direct current stimulation (A-tDCS) on PIS in post-traumatic patients and examine the altered cortical activation after tDCS using nonlinear electroencephalogram (EEG). Methods: The study included 10 patients with post-traumatic PIS. Treatments were divided into two phases: Phase A and Phase B. During Phase A, the patients received 4 weeks of sham tDCS and conventional treatments. During Phase B, these patients received A-tDCS over the prefrontal area and left dorsolateral prefrontal cortex (DLPFC) for 4 weeks (40 sessions) and conventional treatments. CRS-R and apathy evaluation scale (AES) were assessed before Phase A, before Phase B, and after Phase B. The EEG nonlinear indices of approximate entropy (ApEn) and cross approximate entropy (C-ApEn) were also calculated. Results: After A-tDCS treatment, CRS-R and AES were improved significantly. ApEn and C-ApEn results showed that the local cortical connection of bilateral sensorimotor areas with their peripheral areas could be activated by affected painful stimuli, while bilateral cerebral hemispheres could be activated by unaffected painful stimuli condition. Linear regression analysis revealed that the affected sensorimotor cortex excitability and unaffected local and distant cortical networks connected the sensorimotor to the prefrontal area play a major role in AES improvement. Conclusions: A-tDCS over the prefrontal area and left DLPFC improves PIS. The recovery might be related to increased excitability in local and distant cortical networks connecting the sensorimotor area to the prefrontal area. Thus, tDCS may be an alternative treatment for post-traumatic PIS.